2021
DOI: 10.3390/cancers13040789
|View full text |Cite
|
Sign up to set email alerts
|

Second Relapse of Pediatric Patients with Acute Myeloid Leukemia: A Report on Current Treatment Strategies and Outcome of the AML-BFM Study Group

Abstract: Successful management of relapse is critical to improve outcomes of children with acute myeloid leukemia (AML). We evaluated response, survival and prognostic factors after a second relapse of AML. Among 1222 pediatric patients of the population-based AML-Berlin–Frankfurt–Munster (BFM) study group (2004 until 2017), 73 patients met the quality parameters for inclusion in this study. Central review of source documentation warranted the accuracy of reported data. Treatment approaches included palliation in 17 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 33 publications
7
21
0
Order By: Relevance
“…For patients treated curatively, these numbers were 27 ± 5% and 17 ± 4%, respectively. This is in line with recently published findings of Rasche et al 11 who found that 5-year pOS was 15 ± 4% in their cohort of 73 patients with a second relapse. These findings are also in line with work of Zwaan et al on the effectiveness of Mylotarg for treating refractory first or second relapsed paediatric AML.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For patients treated curatively, these numbers were 27 ± 5% and 17 ± 4%, respectively. This is in line with recently published findings of Rasche et al 11 who found that 5-year pOS was 15 ± 4% in their cohort of 73 patients with a second relapse. These findings are also in line with work of Zwaan et al on the effectiveness of Mylotarg for treating refractory first or second relapsed paediatric AML.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to what has been identified for T A B L E 4 Multivariable Cox regression analysis of factors influencing survival in overall cohort of patients with either a refractory first relapse or a second relapse (n = 157). All patient and disease characteristics were gathered at time of initial diagnosis with the exception of: timing of relapse, type of third-line treatment, relapse site, and occurrence of early death which were determined at or following relapse first relapse 5,7,8,20 and what was recently identified by Rasche et al 11 for second relapse, time to relapse and third-line treatment with chemotherapy and SCT were the most important predictors of favourable prognosis in our patient cohort. The latter finding must be interpreted with caution due to the bias inherent in comparing patients who did and did not receive SCT.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, 5-year pOS reached 37% for those patients (15% of the whole cohort) who received chemotherapy and hematopoietich stem cell transplantation (HSCT) as third-line therapy. These data are in line with those of a similar study by Rasche et al 2 reporting on a cohort of 73 patients with a second relapse, with 5-year pOS of 15 (4)%. Among factors influencing prognosis, late relapse (defined as >12 months from diagnosis) was correlated with an improved survival, while FMS-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) mutations (not considering those associated with nucleophosmin 1 [NPM1] mutations) were associated with worse prognosis.…”
supporting
confidence: 92%
“…To achieve this, the results of the AML-BFM 2004 trial have been re-analyzed. Based on the genetic characteristics and augmented by the treatment response to the 1st and 2nd induction, three risk groups could be defined [58].…”
Section: Allohsctmentioning
confidence: 99%